Museu Afro Brasil: estudo de caso da educação patrimonial sob uma perspectiva identitária - Santos, Letícia Cassiano dos (2021)
This undergraduate thesis aimed to study the educational activities carried out at the Afro Brazil Museum located in Ibirapuera Park in São Paulo, to analyze if and how the institution carries out actions that promote the search or rescue of an individual's cultural identity through of their ethnicity represented in the museum. The methodology of this work is exploratory, at first, through systematic observation, the aim was to recognize and detail the museum and its exhibitions; second, a structured interview was carried out with one of the museum's educators to analyze how heritage education takes place in guided tours of the museum; thirdly, a documental analysis of the museum plan, activity plan and other documents available from the institution was carried out, to gather data on the museum's visitation. Finally, due to the pandemic scenario, a second systematic observation was carried out, this time in a virtual environment, where the researcher can describe the methods used in a virtual mediation. Since the methodology is structured according to the objectives of the work, it was possible to affirm that the Afro Brazil Museum carries out in its guided mediations an educational method based on Paulo Freire, similar to heritage education and this one starts from questioning to instigate the critical sense of the visitors; the museum has data on visitation but does not present data on the ethnicity of its visitors, going against the grain with one of its objectives, which is to increase the esteem of black youths; the museum addresses the issue of racism, but with an appreciation bias, not emphasizing the suffering that this ethnic group has experienced and lives, but the museum can be a tool against racism as it carries out activities that help to break down prejudices present in society, which is one of the social functions of museums.